Analisis Xpert® -Carba-R pada Skrining Enterobacterales Resisten Karbapenem di Unit Perawatan Intensif di Rumah Sakit Rujukan Nasional di Jakarta - Yulia Rosa Saharman; Nina Sania; Dita Aditianingsih (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2024)
Introduction: Carbapenem-resistant Enterobacterales (CRE) represent a significant global health problem due to their high resistance to antibiotics. Traditional methods for identifying resistance genes, such as Real-Time PCR (RT-PCR), are accurate but time-consuming and involve complex techniques. This study aimed to compare the Cepheid Xpert® Carba-R test with RT-PCR, used as the gold standard, to determine its effectiveness in rapidly identifying carbapenem resistance genes in CRE. Method: The study was performed from January to June 2022, involving patients admitted to the Intensive Care Unit (ICU) at Dr. Cipto Mangunkusumo National Hospital. Rectal or perirectal swabs were collected upon ICU admission. If patients tested negative for CRE upon admission, repeat swabs were taken at discharge or death, with a maximum length of stay (LOS) of 14 days in the ICU. Genotypic identification of carbapenem resistance genes, including KPC, NDM, OXA-48, VIM, and IMP, was performed using the Cepheid Xpert® Carba-R and compared to RT-PCR. Additionally, phenotypic identification through bacterial culture was performed using the Vitek method. Result: Out of 102 ICU patients, 10.23% (22/215 isolates) were found to be positive for CRE, with the most common bacterial isolates being Escherichia coli (148/215, 68.83%) and Klebsiella pneumoniae (53/215, 24.65%). CRE was found in 1 of 148 E. coli isolates (0.67%) and in 21 of 53 K. pneumoniae isolates (39.62%). The most frequently detected carbapenem resistance gene was OXA-48 (16/22, 72.73%), followed by NDM (6/22, 27.27%). The Xpert® Carba-R test demonstrated a sensitivity and specificity of 100%, with positive predictive value (PPV) and negative predictive value (NPV) both equal to 1. A discrepancy was observed between the phenotypic and genotypic identification, with 27 phenotypically identified CRE isolates compared to 22 genotypically confirmed ones. Conclusion: The Cepheid Xpert® Carba-R test provides a reliable, rapid alternative for identifying carbapenem resistance genes in CRE, demonstrating perfect sensitivity and specificity in this study. This study indicates that Xpert® Carba-R can be an alternative in the rapid identification of CRE resistance genes.